Modern diagnostic potentials of studying structural and functional changes of the retina and the optic nerve in multiple sclerosis patients - A. Zh. Fursova; M. Yu. Zubkova; M. A. Vasilyeva; Yu. A. Gamza; N. A. Malkova; A. I. Prokaeva; F. K. Rabota (Российский офтальмологический журнал)
Purpose: to study significant functional and structural changes in the retina and the intraocular section of the optic nerve in multiple sclerosis (MS) patients and analyze how they are interrelated with electrophysiological changes in the visual analyzer.Materials and methods. The study included 44 patients (88 eyes): group 1 (26 eyes) with MS duration ≤ 5 years and no history of optic neuritis (ON); group 2 (30 eyes) with MS duration from 6 to15 years and no history of ON; and group 3 (32 eyes) with MS duration ≤ 15 years with a history of ON. All patients underwent a complete ophthalmological examination and optical coherence tomography and had visually evoked potentials (VEP) and static automated perimetry registered.Results. A decrease in functional and structural parameters progressing with the duration of MS was revealed. In particular, best corrected visual acuity (BCVA) fell to 0.860 ± 0.075, the photosensitivity index MD maximally fell to -3.78 ± 0.95 dB, the strength of the P100 wave amplitude dropped to 7.84 ± 2.98 μV, the latency index of VEP rose to 124.21 ± 1.36 ms, the thickness of GCL + IPL fell to 65.69 ± 7.85 μm, and RNFL thickness averagely fell a low as to 80.25 ± 8.81 μm. When analyzing the topography of GCL + IPL decrease by sectors, the maximum value was revealed in the upper temporal segment (67.63 ± 7.89 μm). Sectoral changes in RNFL arranged in descending order of thickness showed the following sequence: lower upper nasal temporal. As the disease progressed, structural and functional changes were accompanied by an increase in the depth and a decrease in the thickness of the lamina cribrosa, with a maximum value revealed in the group with prior ON (239.00 ± 11.93 μm). Strong correlations were found in all study groups between (1) ave. GCL + IPL and ave. RNFL (r = 0.69; 0.64; 0.88, p < 0.03), (2) ave. GCL+IPL and BCVA (r = 0.86; 0.75; 0.78, p < 0.05), (3) MD and ave GCL + IPL (r = 0.52; 0.69; 0.71, p < 0.03), and (4) MD and ave. RNFL (r = 0.67; 0.61; 0.66, p < 0.05), as well as between the parameters of the lamina cribrosa and the markers under study.Conclusion. Significant functional and structural changes in the retina and the optic nerve were detected, correlating with the duration of the disease and with the clinical features of the course of multiple sclerosis. The presence of ON in history was accompanied by more pronounced changes, which can be considered as an important additional aggravating factor of the disease.